Performance enhancement of 5G Network using NB-IoT with LTE-M and Novel RASS Algorithm - Sakib, Md. Nazmur; Islam, Md. Shamiul; Islam, Md. Rifatul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022